A STUDY ON THE WELL-BEING OF TEACHER TRAINEES OF IASE, MIZORAM (International Journal of Food and Nutritional Sciences, 2022)
This study was conducted to find out the well-being of teacher trainees of IASE, Mizoram i.e., B.Ed students. The sample of the study comprised of 150 teacher trainees of IASE selected by using stratified random sampling method. Well-Being Scale (WBS-RK) developed by Dr. Ripenjeet Kaur (2014) was used to collect the data. The findings of the study reveal that majority of the teacher trainees i.e., 57.33% has below average well-being and there is a significant difference between gender and language and science pedagogy teacher trainees on their well-being. The finding also shows that 50% of teacher trainees believes mental health concerns are the biggest contributor to their negative well-being and 86.67% of the teacher trainees also believes that developing a growth mindset is the best way to improve their well-being.